Digital distance education in the pandemic COVID-19 (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A documentary review was made of the scientific production registered in the Scopusdatabase regarding the study of Digital Distance Education in the COVID-19pandemic worldwide, with the purpose of knowing the main characteristics of thegeneration of new knowledge on the aforementioned topic. The information to beanalyzed is provided by Scopus through its Search tool, by means of which the data isfiltered in such a way that a total of 1,069 papers published in high impact journals areobtained, referring to distance education during the COVID-19 pandemic. Due to itsnature, the temporal delimitation is defined by the two semesters of 2020 and the f irstsemester of 2021. The bibliometric review is performed on the basis of these data,which are classified according to their area of knowledge, country of origin andaffiliation. Once the information is classified, certain papers are analyzed from abibliographic perspective to know and define the position of different authors withrespect to the proposed topic.